(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The article examines the conceptual approaches of representatives of different economic schools to the problem of poverty, studies the criteria for its measurement, classifies poverty by categories and reasons, and on the basis of this a conceptual model for identifying the poor is developed. According to this model, the category of “working poor” is identified and proposals are made for its identification and reduction.